Unseen Cinema: The Mechanized Eye, Experiments in Technique and Form - Shepard, David (United States : Anthology Film Archives)
Early American avant-garde cinema from 1894-1941. The dynamic qualities of motion pictures are explored by cameramen and filmmakers through novel experiments in technique and form. Early cinematographers James White, "Billy" Bitzer, and Frederick Armitage display experimental shooting styles that wowed audiences. Other independent companies further image manipulation through creative staging, editing, and printing, such as a stunning three-screen film that predates Gance's Napoleon. Experiments by photographer Walker Evans, painter Emlen Etting, musician Jerome Hill, and the film collectives Nykino and Artkino record the world in a continual process of flux. A most extreme approach is realized by Henwar Rodakiewicz with Portrait of a Young Man (1925-31), a monumental study of natural and abstract motions. 18 FILMS: 5 Paris Exposition Films (1900)—James White Eiffel Tower from Trocadero Palace (1900) Palace of Electricity (1900) Champs de Mars (1900) Panorama of Eiffel Tower (1900) Scene from Elevator Ascending Eiffel Tower (1900) Captain Nissen Going through Whirpool Rapids, Niagra Falls (1901)—creators unknown Down the Hudson (1903)—Frederick Armitage & A.E. Weed The Ghost Train (1903)—creators unknown Westinghouse Works, Panorama View Street Car Motor Room (1904)—G.W. "Billy" Bitzer In Youth, Beside the Lonely Sea (c. 1924-25)—creators unknown Melody on Parade (c. 1936)—creators unknown La Cartomancienne (The Fortune Teller) (1932)—Jerome Hill Pie in the Sky (1934-35)—Nykino: Elia Kazan, Ralph Steiner & Irving Lerner Travel Notes (1932)—Walker Evans Oil: A Symphony in Motion (1930-33)—Artkino: M.G. MacPherson & Jean Michelson Poem 8 (1932-33)—Emlen Etting Storm (1941-43)—Paul Burnford Portrait of a Young Man (1925-31)—Henwar Rodakiewicz
Keywords: Fiction films